2020
DOI: 10.48048/wjst.2020.10739
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Data Visualization and Analytics of Highway Accidents

Abstract: Thailand has been ranked as one of the most dangerous countries in terms of death from road accidents, representing ineffective road safety policies. The crucial mission of the Thai government is to provide safety and reduce accidents for road users on the highway system. This paper aims to explore the potential of using Business Intelligence (BI) in accident analysis. The availability of open accident data provides an opportunity for the BI, which can provide an advanced platform for conducting data visualiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Research findings are presented in the following section for better insight and discussion. Sunkpho & Wipulanusat (2020) identified that many transport agencies adopt Tableau software as the visual analytics platform. The following indicate five (5) descriptive and frequency analysis types analysed in this research using Tableau software.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research findings are presented in the following section for better insight and discussion. Sunkpho & Wipulanusat (2020) identified that many transport agencies adopt Tableau software as the visual analytics platform. The following indicate five (5) descriptive and frequency analysis types analysed in this research using Tableau software.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Concerning road crash issues, few studies were conducted using secondary data focusing on the mountainous road network (e.g. Shaadan et al, 2021;Sunkpho & Wipulanusat, 2020). A study comparing mountainous and non-mountainous crash characteristics in Sabah, Malaysia found among factors that increase the odds of crashes along mountainous roads compared with non-mountainous roads including horizontal curve sections, single-vehicle crashes and weekend crashes (Rusdi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation